2018
DOI: 10.2147/tcrm.s165712
|View full text |Cite
|
Sign up to set email alerts
|

Association between leptin gene rs7799039 polymorphism and lipid profile changes induced by isotretinoin treatment in acne patients

Abstract: IntroductionIsotretinoin, a vitamin A-derived medication, is one of the effective treatments for severe acne. However, in a fraction of patients, this treatment causes significant adverse effects. Leptin is a pro-inflammatory cytokine that plays a role in apoptosis of adipose cells and sebaceous lipid metabolism. Thus, genetic polymorphisms in the leptin (LEP) gene may modulate the response to isotretinoin therapy. Here, we explore the contribution of rs7799039 polymorphism of the LEP gene in the adverse effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that isotretinoin can alter human lipid metabolism by significantly reducing sebum production while raising blood lipids ( Khabour et al, 2018 ). Gencebay’s study showed a 36% decrease in sebum levels after 6 months of oral isotretinoin systemic therapy in patients with acne vulgaris ( Gencebay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that isotretinoin can alter human lipid metabolism by significantly reducing sebum production while raising blood lipids ( Khabour et al, 2018 ). Gencebay’s study showed a 36% decrease in sebum levels after 6 months of oral isotretinoin systemic therapy in patients with acne vulgaris ( Gencebay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary of our findings, a cross-sectional study had reported lower AST levels in LEP AA genotype in 200 AV patients treated with oral isotretinoin for 1 month. 35 This controversary may be due to difference in patients’ ethnicity or difference in isotretinoin treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…Our data is accordance with findings of a recent study which reported lower TC levels in LEP rs7799039 CC genotype in Jordanian AV patients who received 40 mg/day oral isotretinoin. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Alzoubi et al 7 revealed that polymorphisms of RARA gene were associated with some common adverse effects of oral isotretinoin. Khabour et al 8 found that lipid parameters and liver enzymes might be modulated by rs7799039 LEP polymorphism. Agamia et al 9 found the nucleocytoplasmic ratio of nonphosphorylated FoxO1 and FoxO3 significantly increased during isotretinoin treatment of acne patients.…”
Section: Discussionmentioning
confidence: 99%